Pluralism and Concentration of Media Ownership: Measurement Issues - Iosifidis, Petros (Javnost-The Public, 2010)
There have been developed various methodologies of measuring media concentration. The appropriate measure depends on the objective of the measurement which might be on the one hand the examination of economic power, or on the other an assessment of whether market structure might restrict diversity in the media industry. Frequently media academics borrow measures that have been developed by economists. Regarding the examination of economic power, economists have used companies’ market share, shares of assets, value-added, sales, advertising revenue or even number of employees in forming an opinion of their bulk in the economy. To overcome the limitations of economic-based measures media analysts have proposed a number of media concentration measures which take into account their importance to the public. This article focuses on the non-economic types of concentration measures and assesses their appropriateness in the broad context of media concentration’s impact on the pluralism and diversity. It suggests that assessing shares in the political/cultural markets is notoriously difficult and concludes that, given that economic power and pluralism (especially in the range of material offered) are closely linked, a combination of economic-based and culturally-based units apply.